Republic of Belarus : Third Review Under the Stand-By Arrangement; Staff Report; Staff Statement; Press Release on the Executive Board Discussion; Statement by the Executive Director. (IMF Staff Country Reports; Country Report ;, 2010)
The staff report on Belarus' Third Review under the Stand-By Arrangement is examined. Belarus is beginning to emerge from the crisis. Output loss has been limited relative to neighbors, inflation has fallen, the foreign exchange market has stabilized, and de-dollarization is under way, which is likely a sign of returning confidence. However, the economy remains vulnerable to external shocks. The current account deficit remains high and reserves low, despite substantial support, including from the IMF. The authorities have taken measures to close a financing gap during the program period created by a shortfall in external financing.